Digestive Health in Sexual and Gender Minority Populations. (14th June 2022) - Vélez, Christopher; Casimiro, Isabel; Pitts, Robert; Streed, Carl; Paul, Sonali
Abstract : It has been over 50 years since the Stonewall Inn Riots in June 1969, a seminal event for the lesbian, gay, bisexual, transgender, queer, intersex, and other sexual and gender-diverse minorities (LGBTQI+, or lesbian, gay, bisexual, transgender, queer, intersex, and everyone else) rights movement. However, sexual and gender minority (SGM) individuals still face discrimination and harassment due to their sexual orientation or gender identity. As such, the National Institute on Minority Health and Health Disparities has identified SGM communities as a "health disparity population." Broadly, there are higher rates of sexually transmitted infections, substance use and abuse, mental health conditions, obesity and eating disorders, certain cancers (breast, cervical, and anorectal), and cardiovascular disease in SGM communities. Transgender patients, especially those of color, are more likely to be uninsured, experience discrimination, and be denied health care than cisgender patients. In addition, SGM individuals have twice the risk of lifetime exposure to emotional, physical, and sexual trauma compared with heterosexuals. It is expected all these factors would negatively affect digestive health as well. This review summarizes the effects of social determinants of health and discrimination on health care access, highlights important digestive diseases to consider in the SGM population, and offers solutions to improve and prioritize the health of these communities. We aim to draw attention to SGM-specific issues that affect gastrointestinal health and spur research that is desperately lacking.